(untitled) (IASH Indian Journal of Arid Horticulture, 2026)
The experiment was conducted during 2024-25 at Rajasthan College of Agriculture, Udaipur, to evaluate the influence of exogenous application of plant growth regulators on vegetative growth and flowering of the guava cv. Allahabad Safeda. Foliar application of 200 ppm gibberellic acid proved most effective in enhancing the tree height (0.63±0.01 m), tree spread (1.57±0.04 m E-W and 1.25±0.06 m N-S) and canopy volume (10.36±0.34 m³). The increase in stem diameter was greatest with 1500 ppm CCC (1.89±0.01 cm). The total chlorophyll content was greatest (2.32±0.12 mg/g) with 2 ppm brassinosteroids. Gibberellic acid (200 ppm) not only hastened the days to first flowering (27.20±0.32 days) but also accelerated the progression to 50% flowering (53.13±0.81 days). The highest fruit set (78.33±0.26%) and fruit retention (60.33±1.53%) and the highest number of flowers/ shoot (7.55±0.04) were recorded with 200 ppm gibberellic acid. The lowest fruit drop (39.67±1.53%) was also recorded in the treatment 200 ppm gibberellic acid. Overall, 200 ppm gibberellic acid was most effective in promoting vegetative growth and flowering in guava.